JABATAN FUNGSIONAL PENERJEMAH SEBAGAI FAKTOR PEMBERDAYAAN PROFESI PENERJEMAHAN DALAM BIROKRASI - Hoed, Benny H. (Jurnal Penerjemahan, 2014)
In today's current reforms, globalization, and regional autonomy contexts, the Indonesian bureaucracy needs to be supported by qualified translators/interpreters. To that end, this article discusses the efforts in institutional and quality development through the Functional Position of Translator (JFP). From the institutional aspect, the article outlines the steps of the Ministry of State Secretariat to establish and implement the JFP. With respect to the quality of the translators/interpreters, the articleunderlines that the JFP is a unique and prone to risk functional position. Therefore, both the Ministry of State Secretariat as well as the translators/interpreters needs to consistently and continuously maintain and enhance the quality of the JFP translators/interpreters.